Cognitive Biases in Investment Decision: Do Education and Income Make a Difference? - Elva Herlianti; Nugraha; Disman; Yayat Supriyatna; Imas Purnamasari (Dinamika Pendidikan, 2024)
This study aims to extensively research the effects of cognitive biases on individual investment decisions. The population of this research is investors in Indonesia and the sampling technique used is random sampling, obtained 574 respondents from 34 provinces in Indonesia. Quantitative data were collected through structured questionnaires and analyzed using multiple linear regression and moderated-moderation model in the PROCESS Procedure for SPSS Version 4.1 by Hayes. Results indicate that herding bias has a negative influence, discouraging investors from following market trends, while loss aversion, framing, anchoring, and mental accounting positively impact investment decisions; these biases are moderated by demographic factors. The findings imply that demographic factors do not interact jointly but operate independently to impact investment behavior. This research is novel in its exploration of moderated-moderation effects to reveal nuanced interactions between cognitive biases and demographics in shaping investment decisions.